Optimal Drainage System Strategy On Gringging Highway, Kediri To Address Water Logging During The Rainy Season - Wijaya, Anindita Fitria; Rahmawaty, Fitry; Siswanto, Eko (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2025)
Rapid land use change in the Jalan Raya Gringging area necessitates a thorough analysis of the drainage system capacity to forecast increased flooding, especially during the rainy season. A mix of descriptive and quantitative methods was employed, including field surveys to measure the physical size and condition of the drainage channels, and hydrological and hydraulic analyses to assess system performance. Hydrological analysis used rainfall data from the past ten years to estimate peak discharge via rational method calculations. The hydraulic analysis evaluated the channel's ability to efficiently convey floodwaters. The results showed that the existing drainage capacity was able to accommodate the flow discharge according to the design discharge with various return periods. However, inundation conditions that occur during the rainy season are caused by elevation differences between the channel and the road surface, so as an effort to increase the efficiency of the drainage system and reduce the risk of inundation, it's recommended that the application of infiltration wells as a complementary strategy that serves to reduce the volume of surface inundation and can strengthen the effectiveness of the existing drainage system. This research expected to contribute to the development of SuDS-based adaptive drainage system planning.